Physical Therapy and Research in Patients with Cancer - Morishita, Shinichiro; Inoue, Junichiro; Nakano, Jiro.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This collection of chapters describes in detail the physical therapy research in patients with various types of cancers to help medical professionals and physical therapists help improve the physical function, activity of daily living, quality of life, the survival rate in cancer patients and cancer survivors. It provides not only information on rehabilitation but details on physical therapy cancer research and research methods. The book provides practical skills to treat the patients and to create useful and effective physical therapy programs by giving step-by-step tutorials to help readers learn various techniques. Along with presenting an introduction to physical therapy of cance and new findings, the authors provide recommendations on each cancer therapy. Physical Therapy and Research in Patients with Cancer is aimed at physical therapists and student physical therapists. Undergraduate and postgraduate students also can use our book to understand the basics and get up-to-date information. By sharing the latest research with our readers, the book creates a foundation for further development in this field of study. .
Part 1 Physical Function and Health Related Quality of Life -- 1 Physical function and health related QOL in cancer survivors -- 2 Physical function and health-related quality of life after breast cancer surgery -- 3 Physical function and health-related quality of life in patients with gastrointestinal cancer -- 4 Physical function and health related QOL in surgically treated patients with malignant pleural mesothelioma -- 5 Muscle mass, cachexia, and health-related quality of life in patients with hematologic malignancies -- 6 Exercise capacity and health-related quality of life in patients after lung resection for non-small cell lung cancer -- Part 2 Physical Exercise -- 7 Effect of physical exercise on physical function and survival rate in cancer patients -- 8 Exercise therapy on muscle mass and physical function in patients undergoing allogeneic hematopoietic stem cell transplantation -- 9 Physical exercise and immune function in patients with hematological malignancies -- 10 Exercise protocols for counteracting cancer cachexia-related declines in muscle mass and strength and the clinical assessment of skeletal muscle -- 11 Physical Exercise and Skeletal Muscle Adaptation in Cancer Cachexia -- 12 Physical function and physical activity in patients with advanced lung cancer -- 13 Physical Activity in Patients with Breast Cancer -- Part 3 Physical Function and Other Symptom -- 14 Multiple frailty in elderly patients with cancer -- 15 Postoperative complications in patients with esophageal cancer -- 16 Cancer-related lymphedema and obesity -- 17 Cancer-related pain and effects of non-pharmacologic intervention -- 18 Nutrition and daily activities in older patients after gastrectomy -- 19 Frailty and mental health in older patients with gastrointestinal cancer -- 20 Physical function and nutrition in patients with hematological malignancies -- 21 Physical Function and Nutrition in Patients with Esophageal Cancer and Head and Neck Cancer -- Part 4 Skeletal Muscle -- 22 Skeletal muscle oxygenation in patients with malignant hematopoietic disease -- 23 Sarcopenia and physical performance in patients with cancer -- 24 Cachexia and postoperative outcomes in elderly patients with gastrointestinal cancer -- 25 Mechanism of skeletal muscle atrophy using a mice cancer cachexia model.
Keywords: Physical therapy; Cancer$1 (BTreatment.s; Medical sciences; Hematology; Oncology; Physiotherapy; Cancer Therapy; Health Sciences; Hematology; Oncology; Neoplasms -- psychology; Neoplasms -- therapy; Palliative Care